Serological survey of small mammals in a vesicular stomatitis virus enzootic area - Jiménez Sánchez, Carlos (1996)
Small nmamnnmals were captured in a Costa Rican dairy farm located ium a vesicular stouiiatitis virus (VSV) enzootic focus, in order to determine which species were naturally infected by this virus. Monthly captures were performed from March 1989 to February 1990. Eighty-four individuals belonging to the orders Rodentia (n = 52), Insectivora (n = 31) and Marsupiahia (n = 1) were captured. Only Sigrnodon hispidu.s had neutralizing antibodies to VSV; among 21 ammimnals, six had antibodies to Indiana, one to New Jersey, and two to both serotypes. In addition, groups of 40 sentinel mice (Mu.s musculus, strain C3H) were placed in cages distrihmmted through- out the farm. Each group was exposed for 1 mo over a period of 1 yr. None of 312 sentinel mice developed antibodies against eitimer VSV serotype. Based on these results, we believe that S. hispklus might be part of the natural cycle of VSV in timis enzootic focus. Caged Mus musculus (10 mmot seem appropriate for monitoring VSV activity in this area. (10 mmot seem appropriate for monitoring VSV activity in this area.